CHILDREN'S SONGS CREATION TECHNIQUE DEVELOPMENT FOR KINDERGARTEN TEACHERS - Suryadi Suryadi; Usep Kustiawan (Informascope, 2018)
This study aims to produce a creation in a form of techniques to create decent children's songs used by kindergarten teachers. In addition, this study also aims to produce an advance creation in the form of technical guidebooks that can facilitate kindergarten teachers in creating children's songs. Data obtained from experts' evaluations consisting of one material expert and two teaching experts. In addition, the data were also obtained from product trial conducted in three steps; individual trial conducted on Al-Fadholi kindergarten and kindergarten group III - IGTKI Lowokwaru sub-district Malang Indonesia. One group pretest posttest design is conducted within the product trials. Based on the experts' evaluations data and product trial related to the feasibility and effectiveness of the product obtained the result of creating children's songs technique for kindergarten teachers is very feasible and effective to be applied. It is shown from the overall score of 1368 with percentage of 85,5% in excellent category. From the description, it can be defined that result of creating children's songs technique for kindergarten teachers is very feasible and effective to be applied. The score is 688 with percentage of 86% in excellent category. For the technical guidebook of children's songs trial result shows that posttest's result is better than the pretest's result, quantity is obtained with a score of 60 with a percentage value of 81.08% in a very good category, and obtained a score of posttest 211 with a percentage value of 71.28% in good category. This indicated that technical guide product obtained can ease kindergarten teachers to understand the process of creating children's songs, thus the development required to be done.